Upaya Peningkatan Kapasitas Pengelolaan Jurnal Ilmiah Online Perguruan Tinggi di Wilayah Kabupaten Cilacap - Oman Somantri; Ganjar Ndaru Ikhtiagung; Linda Perdana Wanti; Muhammad Nur Faiz; Erna Alimudin (Madani : Indonesian Journal of Civil Society, 2022)
Limitations in knowledge in managing an online scientific journal following the standards and skill level possessed by journal managers, mainly operating the Open Journal System (OJS) application, are obstacles faced by several universities in the Cilacap Regency area. The solution proposed in this article is a training activity in the form of a workshop held for managers of higher education journals in the Cilacap area to increase knowledge and skills in managing journals using OJS. The stages of the activity are carried out through several stages, namely the planning stage, the implementation stage, the activity evaluation, and last stage is the mentoring stage. The results of the training provided a fairly good impact and affected the level of knowledge of the participants in managing OJS-based journals. The results of the assistance from the activities show an increase in interest for universities that do not yet have journals to want to make them, in addition to a rise in the status of journals that have been published to become accredited journals.